‘Communication, that is the key’: a qualitative investigation of how essential workers with COVID-19 responded to public health information - Yanbing Chen; Claire Buckley; Elizabeth Alvarez; Conor Buggy; Mark Roe; Mary Codd; Anne Drummond; Carolyn Ingram; Penpatra Sripaiboonkij; Carla Perrotta; Mary Archibald; Vicky Downey; et al. (BMJ Open)
Objectives To understand how essential workers with confirmed infections responded to information on COVID-19.Design Qualitative analysis of semistructured interviews conducted in collaboration with the national contact tracing management programme in Ireland.Setting Semistructured interviews conducted via telephone and Zoom Meetings.Participants 18 people in Ireland with laboratory confirmed SARS-CoV-2 infections using real-time PCR testing of oropharyngeal and nasopharyngeal swabs. All individuals were identified as part of workplace outbreaks defined as ≥2 individuals with epidemiologically linked infections.Results A total of four high-order themes were identified: (1) accessing essential information early, (2) responses to emerging ‘infodemic’, (3) barriers to ongoing engagement and (4) communication strategies. Thirteen lower order or subthemes were identified and agreed on by the researchers.Conclusions Our findings provide insights into how people infected with COVID-19 sought and processed related health information throughout the pandemic. We describe strategies used to navigate excessive and incomplete information and how perceptions of information providers evolve overtime. These results can inform future communication strategies on COVID-19.